Mafqūd and Fasakh in the Writings of Muslim Jurists and Provisions of Malaysian Federal Territory Islamic Family Law: The Case of MH 370 Missing Plane - Mahmud, Mek Wok; Mokhtar, Siti Zulaikha binti (Intellectual Discourse, 2017)
In Islam, there are various forms of dissolution of marriages that are permitted to avoid the greater evil which may result from their continuance. Wives are granted the right to dissolve a marriage in order to protect their rights, particularly in the case missing husbands, either alive or dead. This is known as mafqūd, or missing person. Therefore, the objective of this study is to discuss the concept of fasakh and mafqūd in accordance with the views of Muslim jurists and the provisions of Islamic family law in Malaysia. This paper also aims to analyse both those views in the context of the MH 370 incident. This study uses the qualitative method, by collecting data obtained by means of information gathering within the resources of the library and authoritative websites. From the study, it is shown that the wife can apply for divorce on the basis of fasakh when it is diffi cult to prove the status of a missing husband. In other words, rulings applicable to fasakh can be activated in the case of mafqūd. Further discussions are expected to fi nd the best period of presumption of death, since it is based on ijtihād or the discretion of lawmakers.